(untitled) (NAU Journal of Technology and Vocational Education, 2026)
The integration of sustainability into competency-based education has become a global imperative, yet significant gaps persist between policy intentions and classroom realities. This study explores the lived experiences of Consumer Science teachers in Eswatini as they go through the complex process of embedding sustainability within competency-based curricula in secondary education. Despite policy frameworks emphasizing sustainability education, limited research examines the subject-specific challenges teachers encounter in translating these mandates into meaningful pedagogical practice. Guided by four research questions, this qualitative descriptive research explores the practical barriers, innovative strategies and enabling factors that shape Consumer Science teachers’ implementation of sustainability competencies. The population for this study comprises all the 48 Consumer Science teachers in secondary schools within the Manzini region. A sample of 15 Consumer Science teachers was selected using purposive sampling technique to ensure participants had experience in teaching sustainability-related content within competency-based frameworks. Data were collected through in-depth semi-structured interviews and document analysis to capture rich, contextual insights into teachers’ experiences. Data were analysed using thematic analysis, facilitated by the NVivo software. Findings reveal how teachers adapt existing resources, utilize household materials for practical exercises, and employ collaborative learning approaches to overcome resource constraints. The study highlights the critical role of teacher agency and innovation in bridging the policy-practice gap, including the integration of sustainability into daily school routines through waste management initiatives and school gardens, as well as professional networking for resource sharing. The study recommends context-sensitive approaches that acknowledge resource realities while empowering teachers as key agents of transformative sustainability education.